AB0635 Gastrointestinal quality of life index (GIQLI) in patients with primary sjÖgren's syndrome. (23rd January 2014) - Bitik, B.; Tufan, A.; Mercan, R.; Tezcan, M.E.; Kaya, A.; Ozturk, M.A.; Haznedaroglu, S.; Goker, B.
Abstract : Background: Primary Sjögren's Syndrome (pSS) is a chronic, inflammatory autoimmune disorder, characterized by lymphocytic infiltration of the exocrine glands, leading to decrease of glandular secretion. Gastrointestinal (GI) involvement is reported to be common in pSS patients as increased frequency of irritable bowel syndrome, functional dyspepsia, impaired gastric emptying, chronic atrophic gastritis and Celiac disease 1, 2, 3, 4 . Decreased salivary function as well as possibly reduced GI digestive secretions due to exocrine destruction in pSS patients might impair GI tract functions, resulting in complaints amenable to this system. The GIQLI 5 is a 36-item patient reported outcomes instrument designed to assess GI-specific health-related quality of life in clinical practice and clinical trials of patients with GI disorders. It has five domains (GI symptoms, emotion, physical function, social function and medical treatment) and subscores range from 0-4 while the total score range from 0-144. Higher scores mean better GI health-related quality of life. Objectives: To evaluate the gastrointestinal quality of life in patients with pSS. Methods: Thirty-six patients with pSS (all female, age (mean±SD) 49.6±5.8 years) and 44 healthy female subjects without a medical problem were enrolled. The Turkish version of the GIQLI questionnaire with minor wording modifications was utilized for the study. All participants completed the self-administered questionnaire in a private room at the clinic. Only the score for GI domain along with the total score was analyzed. At a later stage the GI symptoms were assessed by dividing the symptoms as upper and lower GI part symptoms. Results: The total GIQLI score was not different between the patients with pSS and the control group (86.9±19.5 vs 86.6±20.3, p>0.05). The gastrointestinal domain score also did not differ between the two groups (50.5±11.5 vs. 50.0±12.1, p>0.05) Conclusions: Gastrointestinal quality of life in patients with pSS seems to be similar with the healthy population in contrast with expected. Our results suggest GI involvement is not common in pSS and need to be confirmed in studies with large patient numbers. References: Ohlsson B, et al. Functional bowel symptoms and GnRH antibodies. Common findings in patients with primary Sjögren's Syndrome but not in Systemic Sclerosis. Scand J Rheumatol 2009; 38:391-3 Maury CPJ, et al. Atrophic gastritis in Sjögren's Syndrome. Morphologic, biochemical, and immunologic findings. Arthritis Rheum 1985;28:388-94 Luft LM, et al. Autoantibodies to tissue transglutaminase in Sjögren's syndrome and related rheumatic diseases. J Rheumatol 2003;30: 2613-9 Hammar O, et al. Impaired gastric emptying in primary Sjogren's syndrome. J Rheumatol 2010;37:2313-8 Eypasch E, et al. Gastrointestinal Quality of Life Index: development, validation and application of a new instrument. Br J Surg. 1995;82:216-22. Disclosure of Interest: None Declared